Diálogos poético-plásticos e natureza em Helena Kolody e Miguel Bakun: a poesia das palavras e das cores - Kroin, Vanderlei (2017)
This work aims to perform a comparative study between poetry and painting, focusing on two Slavic-Brazilian artists of the 20th Century: the poet Helena Kolody and the plastic artist Miguel Bakun, unveiling nature’s presence in the work of both of them. This work is guided by the premises of compared literature and interartistic studies, based on authors such as Carvalhal (1986), Coutinho (2003), Nitrini (2010), Pageaux (2011). Also regarding the interartistic theoretical suppositions: Lessing (2011), Muhana (2002), Da Vinci (2000), Praz (1982), as well as authors like Bastide (1979), Candido (2000), Kothe (1981), Bosi (2000a; 2000b), Hauser (1998), Gombrich (1988), Paz (1991; 1996), among other scholars that discuss in their works and studies the relations between artistic pieces and society, social aspects of arts, aspects of the nature of paintings, of literature, arts and the (inter)relations that they maintain with history and the social environment from which they have emerged. It is known about the convergences and divergences between the two language systems: verbal and visual, but having them as artistic systems that speak from man to man, we intend to discuss their correlation. Still, registering the comparison between Helena Kolody and Miguel Bakun, two artists born in rural Paraná, at the heart of Slavic culture, thus, in a way at the margin of the modernist canon, which meets the current perspectives of comparative studies, in other words, unveiling works and authors originated from areas regarded as peripheral from the globe. We will also seek to observe the stablished relation between the artist with the nature of the practiced art, poem and painting, once the subject, poet or painter, leaves trails of his/her empiric world in his work, as the work configures itself as timeless by the aesthetics operated by the language system that constitutes it.